The Multivariate Role of Character Strengths on Psychological Well-Being: A Study of High School Students in Indonesia - Ayu Riana Sari; Winna Andini Handayani (Universitas Katolik Soegijapranata, 2026)
Addressing adolescent problems tends to focus on problematic behaviour and pays less attention to positive aspects of adolescents that can be used as strengths to improve their psychological well-being. This study aims to examine the contribution of character strengths to adolescent psychological well-being. The research method used is quantitative research with a non-experimental design. Data were obtained from 822 students from 25 public high schools in Bandung City using the Values in Action-Youth questionnaire to measure character strengths and The Ryff Scales of Psychological Well-being to measure adolescent psychological well-being. Data analysis used multiple regression with stepwise regression calculations. Collectively, character strengths explained a significant 56.9% of the variance in psychological well-being (R² = 0.569, p 0.001). Among these, gratitude emerged as the most dominant single predictor, accounting for 32.5% of the variance (B = 3.26, β = 0.23, p 0.001, 95% CI [2.42, 4.11]). Unique findings indicate that although spirituality had the highest average score, its contribution to well-being tended to be reduced when interacting with other characters. The results of this study can be used to develop programs improving adolescent psychological well-being by strengthening positive character traits typical of adolescents.